The (non-)translatability of the Holy Trinity - Müller, Retief (HTS teologiese studies, 2019)
This article considers the ambiguous translatability of the Christian doctrine of the Holy Trinity. The theme of the Trinity, as a central Christian doctrine, is brought into conversation with the so-called ‘translatability thesis’ regarding Christian history, which has been particularly expounded upon by Lamin Sanneh and Andrew Walls. Does the translatability of the gospel also imply the translatability of the Trinity, or is the equation not that straightforward? In answering this question, specific reference is made to early church formulation and controversy surrounding the theme, as well as attention to specific attempts at translation or interpretation in the modern and contemporary forms of Christianity. The article acknowledges the problematic nature of Trinitarian translatability and concludes that such translatability is nonetheless possible as long as a static conception of Trinitarian doctrine could be avoided.